Navigating the manufacturing, testing and regulatory complexities of regulatory T cells for adoptive cell therapy - Pikor, Larissa A.; Arivazhagan, Sindhu; Mendicino, Michael; Sathiamoorthy, Sarmitha (Frontiers in Immunology, 2025)
Regulatory T cells (Tregs) are a small, unique subset of suppressive T cells that play a pivotal role in regulating the immune system by maintaining tolerance to self-antigens and preventing autoimmune disease. Adoptive transfer of Tregs for the treatment of autoimmune disorders such as arthritis and allergic airway inflammation, graft-versus-host disease (GvHD) and rejection following transplant have shown promise in early phase clinical trials. Despite over a decade of clinical manufacturing, there remains significant manufacturing and testing complexities for this class of therapies, including the need for specialized facilities and highly trained personnel that make clinical and commercial supply challenging. In this review, we discuss the current Chemistry, Manufacturing and Controls (CMC) and regulatory complexities and challenges to the development and commercialization of Treg therapies. Some of these are specific to Tregs while others are broadly applicable to the field of cell-based therapy. Discussion topics include the importance of starting material selection, the availability of GMP quality reagents and material, isolation and characterization of regulatory T cells, cGMP manufacturing considerations and limitations, the complexity of testing, release and distribution of cell-based therapies, as well as the regulatory challenges associated with Treg therapy. Treg cell therapies can be fraught with technical challenges which are mirrored by a sponsor’s ability to meet regulatory requirements. Despite these hurdles, the promise of Tregs as a therapeutic for the treatment of autoimmune and other diseases warrants continued development.